2010
DOI: 10.1001/archinternmed.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination and Vitamin K Antagonist Treatment

Abstract: clinicaltrials.gov Identifier: NCT00222638.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The increase of INRs out of range was not associated with an increase in complications after COVID-19 vaccination. The limited number of complications after COVID-19 vaccination is in line with the literature on post-vaccination complications in both adult and paediatric VKA users [ [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. However, Dutch anticoagulation clinics were encouraged to monitor the anticoagulation status shortly after COVID-19 vaccination, so any necessary dose adjustments could rapidly be made.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The increase of INRs out of range was not associated with an increase in complications after COVID-19 vaccination. The limited number of complications after COVID-19 vaccination is in line with the literature on post-vaccination complications in both adult and paediatric VKA users [ [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. However, Dutch anticoagulation clinics were encouraged to monitor the anticoagulation status shortly after COVID-19 vaccination, so any necessary dose adjustments could rapidly be made.…”
Section: Discussionsupporting
confidence: 73%
“…Stability of anticoagulation after vaccination has mainly been described in the adult and elderly VKA users. In most studies, no effect on the INR after vaccination was observed [ [30] , [31] , [32] , [33] , [34] ]. Only two studies have looked at the percentage of INRs out of range after COVID-19 vaccination [ 6 , 35 ].…”
Section: Discussionmentioning
confidence: 99%